Head-to-head performance comparison of self-collected nasal versus professional-collected nasopharyngeal swab for a WHO-listed SARS-CoV-2 antigen-detecting rapid diagnostic test - Klein, Julian; Krüger, Lisa; Tobian, Frank; Gaeddert, Mary; Lainati, Federica; Schnitzler, Paul; Lindner, Andreas; Nikolai, Olga; Knorr, Britta; Welker, Andreas; Vos, Margaretha de; Sacks, Jilian A.; et al. (medRxiv, 2021)
Background In 2020, the World Health Organization (WHO) recommended two SARS-CoV-2 lateral flow antigen detecting rapid diagnostics tests (Ag-RDTs), both initially with nasopharyngeal (NP) sample collection. Independent head-to-head studies demonstrated for SARS-CoV-2 Ag-RDTs nasal sampling to be a comparable and reliable alternative for nasopharyngeal (NP) sampling. Methods We conducted a head-to-head comparison study of a supervised, self-collected nasal mid-turbinate (NMT) swab and a professional-collected NP swab, using the Panbio Ag-RDT (the second WHO-listed SARS-CoV-2 Ag-RDT, distributed by Abbott). We calculated positive and negative percent agreement and, compared to the reference standard reverse transcription polymerase chain reaction (RT-PCR), sensitivity and specificity for both sampling techniques. Results A SARS-CoV-2 infection could be diagnosed by RT-PCR in 45 of 290 participants (15.5%). Comparing the NMT and NP sampling the positive percent agreement of the Ag-RDT was 88.1% (37/42 PCR positives detected; CI 75.0% - 94.8%). The negative percent agreement was 98.8% (245/248; CI 96.5% - 99.6%). The overall sensitivity of Panbio with NMT sampling was 84.4% (38/45; CI 71.2% - 92.3%) and 88.9% (40/45; CI 76.5% - 95.5%) with NP sampling. Specificity was 99.2% (243/245; CI 97.1% - 99.8%) for both, NP and NMT sampling. The sensitivity of the Panbio test in participants with high viral load (> 7 log10 SARS-CoV-2 RNA copies/mL) was 96.3% (CI 81.7% - 99.8%) for both, NMT and NP sampling. Conclusion For the Panbio Ag-RDT supervised NMT self-sampling yields to results comparable to NP sampling. This suggests that nasal self-sampling could be used for scale-up population testing.
Gesehen am 30.04.2021